First-principles study of the electronic and magnetic properties of monolayer CrOBr. (January 2022) - Xu, Chunyan; Zhang, Jing; Guo, Zexuan; Yuan, Xiaoxi; Tian, Yu
Abstract: Two-dimensional (2D) materials with intrinsic ferromagnetism, a sizable magnetic anisotropy energy (MAE) and large spin polarization are desirable for realizing the practical spintronic applications. Base on first-principles calculations, the stability, electronic and magnetic properties of monolayer CrOBr are systematically investigated. Monolayer CrOBr is ferromagnetic semiconductor with a band gap of 1.547 eV, it possesses in-plane magnetic anisotropy with a value of −0.017 meV/formula unit (f.u.). The band gap of monolayer CrOBr can be regulated in the range of 1.547-1.145 eV by applying biaxial tensile strain. Monolayer CrOBr changes from FM state to AFM state when tensile strain increases to 8%. The MAE of monolayer CrOBr reaches a large value of −0.057 meV/f.u. at tensile strain of 8%, which is enhanced by 235% compared to that of unstrained system. The tunable MAE and electronic structure indicate that monolayer CrOBr may be a promising candidate in spintronic devices. Highlights: Monolayer CrOBr is FM semiconductor with in-plane magnetic anisotropy of −0.017 meV/formula unit. The MAE can be enhanced by 235% when biaxial tensile strain reaches 8%. The band gap varies in the range of 1.547-1.145 eV by applying biaxial tensile strain.